ORGANIZATIONAL PEDAGOGICAL PRINCIPLES OF LEADING STUDENTS IN CLASSROOM AND OUTSIDE-SCHOOL ACTIVITIES (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The main task of the education sector is to provide our youth with indepth knowledge in accordance with the international educational standards, to educate them in the spirit of love for the Motherland and loyalty to the ideals of national independence. In this article, we have studied the organizational and pedagogic foundations of leading students in their classroom and extracurricular activities for quality and creative learning.